Epitaxial Cobalt Oxide Films with Wurtzite Structure on Au(111). Issue 11 (10th November 2021) - Ammon, Maximilian; Baumann, Sara; Kißlinger, Tilman; Rieger, Janek; Fauster, Thomas; Redinger, Josef; Hammer, Lutz; Schneider, M. Alexander
Abstract : Cobalt oxide is a versatile material found in different polymorphs. In article number 2100383, Lutz Hammer, M. Alexander Schneider, and co‐workers demonstrate the growth of the wurtzite cobalt oxide polymorph as a thin but bulk‐like film; in the growth method, it is pivotal to establish the correct oxygen partial pressure during the deposition of metallic Co and carefully adjust the post‐deposition thermal treatment while controlling the crystallographic structure. The structure and properties of the material are determined using low‐energy electron diffraction, ultraviolet photoelectron spectroscopy, and scanning tunneling microscopy.